Experimental investigations of the phase change impacts on flash boiling spray propagations and impingements. (15th March 2022) - Qiu, Shuyi; Xiao, Di; Zhang, Xuan; Wang, Shangning; Wang, Tongyang; Li, Xuesong; Xu, Min
Highlights: Impingement fuel mass does not necessarily increase by flash boiling spray collapse. The liquid component that remained in the spray is strongly correlated to superheat level. Low impingement plate temperature suppresses wall film evaporation. Liquid volume flux is a more general criterion to evaluate spray impingement than the penetration distance. Abstract: Flash boiling atomization technique has been considered a potential method for spray breakup performance enhancement utilizing the micro-explosion of superheated liquid. But the strong evaporative features of flash boiling atomization are not thoroughly investigated and understood. For instance, the impact of flash boiling atomization on the liquid mass fraction inside the spray plume and the influence on the formation of spray impingement wall film are not clear. Therefore, this work focuses on the phase change impacts of flash boiling atomization and measures the volume flux of the liquid component during flash boiling atomization using phase Doppler interferometry. This work further investigates the consequence of flash boiling spray collapse in the aspect of spray impingement, with the two-dimensional thickness and temperature distribution measured by laser-induced exciplex fluorescence technique. Both free sprays and impinging sprays with the same settings (and different temperatures) are examined for compassion. This investigation verifies that due to the phase change of flash boiling atomization, the liquid component inside the plume drops significantly so that the wall impingement performance cannot be evaluated with spray penetration length only. Such observations also hold even spray collapse takes place using a multi-hole fuel injector.